Improving Students’ Reading Comprehension of Narrative Text Through Draw Strategy - Jondriantoni (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2023)
The objectives of this study are to know how is DRAW strategy applied in teaching reading comprehension of narrative text and in what ways are students‟ achievement improved after being taught by this strategy. The writer collected the data by using classroom action research. The action research was carried out in some steps. Those steps were pre-elimination test, spiraling the cycle of planning, acting, observing and reflecting. The instruments that were used are tests, observation sheets and questionnaires. DRAW strategy is one of strategies that can be applied in teaching reading. D represents draw as in pull questions out of the box. R is for read to find the answer. A stands for attend as in listen to what classmates say as they discuss answers to drawn questions. And W represents write; students write answers to a selected few questions based on their notes from the class discussion. With DRAW, students work in small groups to discuss a text and respond to questions that involve critical thinking. In short, DRAW strategy encourages higher order thinking, motivates students in gaining information, promotes discussion, encourages listening, and promotes participation. The preelimination test in this classroom action research was used to know the students‟ achievement on reading comprehension of narrative text before conducting the research. In the pre-elimination test, the class‟ mean score was 45.17. In the cycle 1 test, the class‟ mean score was 62.17. And in the cycle 2 test, the class‟ mean score was 74.17. It can be concluded that the class‟ mean score from preelimination test to cycle 1 test improved 37.6% and 64.2% from pre-elimination test to cycle 2 test. In short, the result of each cycle prove that students‟ achievement of reading comprehension was getting better after this strategy was conducted in teaching and learning process. It can be concluded that by using DRAW strategy in reading class, students‟ reading comprehension can be improved. This strategy is a good technique to help students in comprehending English reading texts.